The Obstacles that Parents Encountered when Taking Children to Psychological Clinic in Vietnam - Nguyen Thi Dung (RIRAI Publisher, 2020)
This study aimed to explore difficulties that parents faced when bringing their children to psychological examination in Vietnam through their life stories. The research participants included 5 fathers and 3 mothers having children diagnosed with autism. A preliminary interview prior to the study and in-depth interviews were carried out with their voluntariness. To collect and analyze the data,